Power System Analysis of an Industrial Distribution Network Using ETAP: Load Flow, Short Circuit and Protective Device Coordination Studies (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This project focuses on analyzing an industrial electrical distribution network of a Cement Plant using ETAP software. A detailed Single Line Diagram (SLD) of the plant is modeled in ETAP. Load Flow studies are conducted to determine real and reactive power distribution, voltage profiles, system losses and equipment rating. Short Circuit analysis is used to evaluate fault currents for appropriate equipment rating and protection design. Protective Device Coordination ensures proper fault isolation while maintaining system stability and minimizing disruption. One of the key focuses of this project is to avoid Blackouts in the industry by enhancing system reliability and responsiveness during fault conditions. The objective is to ensure reliable, safe, and efficient power delivery through Load Flow Analysis, Short Circuit Studies, and Protective Device Coordination.